Targeted imaging of EGFR overexpressed cancer cells by brightly fluorescent nanoparticles conjugated with cetuximab. Issue 32 (29th July 2016) - Gao, Meng; Su, Huifang; Lin, Gengwei; Li, Shiwu; Yu, Xingsu; Qin, Anjun; Zhao, Zujin; Zhang, Zhenfeng; Tang, Ben Zhong
Abstract : To improve the treatment efficiency and reduce side effects in cancer therapy, accurate diagnosis of cancer cell types at a molecular level is highly desirable. Abstract : To improve the treatment efficiency and reduce side effects in cancer therapy, accurate diagnosis of cancer cell types at a molecular level is highly desirable. Fluorescent nanoparticles (NPs) are especially suitable for detecting molecular biomarkers of cancer with advantages of superior brightness, easy decoration and high resolution. However, the conventional organic fluorophores, conjugated polymers, and inorganic quantum dots suffer from the drawbacks of aggregation-caused quenching (ACQ), low photostability, and heavy metal toxicity, respectively, which severely restrict their applications in NPs-based fluorescence imaging. To overcome these limitations, herein, we have developed fluorescent nanoparticles based on a t -BuPITBT-TPE fluorophore derived from aggregation-induced emission (AIE)-active tetraphenylethene. Through encapsulating t -BuPITBT-TPE within biocompatible DSPE-PEG and further decorating with a monoclonal antibody cetuximab (C225), the obtained t -BuPITBT-TPE-C225 NPs can be used for targeted imaging of non-small cell lung cancer cells with an overexpressed epidermal growth factor receptor (EGFR). The specific targeting ability of t -BuPITBT-TPE-C225 NPs has been well verified by confocal microscopy and flow cytometry experiments. The t -BuPITBT-TPE-C225 NPs have shown significant advantages in terms of highly efficient red emission, good bio-compatibility, and excellent photostability. This work provides a promising method for precise diagnosis of cancer cells by antibody-functionalized fluorescent NPs with high brightness.